Pengaruh Pelatihan Bantuan Hidup Dasar Terhadap Pengetahuan Siswa Kelas XII Di SMK Baznas Sulsel - Sudarman Sudarman; Akbar Asfar; Irmiatinarahma Pago (Lembaga Layanan Pendidikan Tinggi (LL-DIKTI) Wilayah IX Sulawesi, 2019)
Abstract. Vocational High School Students (SMK) is one part of the community that is competent to be trained in basic life support (BLS), where they are at the age of adolescents who are vulnerable to the emergency situation. This study aims to determine the effect of basic life support training (BLS) on increasing the knowledge of students of class XI SMK Baznas South Sulawesi. This study uses a quantitative approach with a type of quasi experimental research and pre and post test control group design research design. In this design the researcher intervened in two groups. The first group as the treatment group and the second group as the control group. The population in this study were all students of class XI Baznas Vocational High School, amounting to 42 people consisting of 21 intervention groups and 21 control groups. The test used by the Wilcoxon Test was to determine differences in knowledge and skills before and after in both groups. The results showed that there was an effect of basic life assistance training on the knowledge of Class XI Students at the National Baznas Vocational School in South Sulawesi with a value of α = 0.001 (<0.05). There is no effect of givinga guidance on basic life assistance to the knowledge of Class XI Students at South Sulawesi Baznas Vocational School with a value of α = 0.102 (> 0.05). There was no difference in knowledge between students who were given training and those who were not given basic life assistance for Class XI students at South Sulawesi Baznas Vocational School with a value of α = 0.682 (> 0.05). The conclusion of this study was that there was no difference in knowledge of students who were given BLS training and those who were not given BLS training. It is expected that the management of the South Sulawesi Baznas Vocational School will plan BLS training on a regular basis, providing tools and materials such as POM BLS infant, Children and Adults to be used by students to practice BLS actions in order to increase student knowledge in providing BLS to patients / victims of emergency conditions. Abstrak. Siswa Sekolah Menengah Kejuruan (SMK) merupakan salah satu bagian dari masyarakat yang berkompetensi untuk dilatih tentang bantuan hidup dasar (BHD), dimana mereka berada pada usia remaja yang rentan akan situasi kegawatdaruratan tersebut. Penelitian ini bertujuan untuk mengetahui pengaruh pelatihan bantuan hidup dasar (BHD) terhadap peningkatan pengetahuan siswa kelas XI SMK Baznas Sulsel. Penelitian ini menggunakan pendekatan kuantitatif dengan jenis penelitian quasi eksperimen dan desain penelitian pre and post test control group design. Pada desain ini peneliti melakukan intervensi pada dua kelompok. Kelompok pertama sebagai kelompok perlakuan dan kelompok kedua sebagai kelompok kontrol. Populasi dalam penelitian ini adalah seluruh siswa-siswi SMK Baznas Sulsel kelas XI yang berjumlah 42 orang yang terdiri dari 21 orang kelompok intervensi dan 21 kelompok kontrol. Uji yang digunakan Wilcoxon Test adalah untuk mengetahui perbedaan pengetahuan dan keterampilan sebelum dan sesudah pada kedua kelompok. Hasil penelitian menunjukkan ada pengaruh pelatihan bantuan hidup dasar terhadap pengetahuan Siswa Kelas XI di SMK Baznas Sulawesi Selatan dengan nilai α=0,001 (<0,05). Tidak ada pengaruh pemberian panduan tentang bantuan hidup dasar terhadap pengetahuan Siswa Kelas XI di SMK Baznas Sulawesi Selatan dengan nilai α=0,102 (>0,05). Tidak ada perbedaan pengetahuan antara siswa yang diberikan pelatihan dan yang tidak diberikan bantuan hidup dasar Siswa Kelas XI di SMK Baznas Sulawesi Selatan dengan nilai α=0,682 (>0,05). Kesimpulan dari penelitian ini adalah tidak ada perbedaan pengetahuan siswa yang diberikan pelatihan BHD dan yang tidak diberikan pelatihan BHD. Diharapkan pihak pengelola SMK Baznas Sulawesi Selatan melakukan perencanaan pelatihan BHD secara rutin, menyediakan alat dan bahan seperti pantom RJP Bayi, Anak dan Dewasa untuk digunakan siswa praktik tindakan BHD agar dapat meningkatkan pengetahuan siswa dalam memberikan BHD pada pasien/korban kondisi darurat.